A study of Naphthionin in the management of the bleeding defect in patients with thrombocytopenia. Issue 6 (November 1964) - Poller, L.; More, J. R. S.
Abstract : Sodium-α-naphthylamine-4-sulphonate (Naphthionin) appears to shorten the bleeding time in normal subjects and to be of value in the management of the bleeding defect in patients with thrombocytopenia when given by intravenous or intramuscular injection. A good response was achieved in three patients suffering from severe haemorrhage and the prolonged bleeding time in other cases of thrombocytopenia was shortened. There is no evidence that Naphthionin is of value in haemostasis in other patients in whom haemorrhage is not due directly to thrombocytopenia.